Moderating Effect of E-Money Usage on Generation Z Financial Management in a Cashless Society - Vitalia, Theresia Trisna; Noviarty, Helisa; Haryono, Haryono (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The rapid growth of technology, particularly in financial technology, has given rise to the phenomenon of a cashless society and the routine practice of citizens conducting cashless transactions. One notable growth in cashless payments is electronic money, which has become a trend in daily transactions. In this regard, Generation Z, born in the digital technology era, is not exempt from this phenomenon, thereby allowing for an increase in the use of e-money. This study aims to analyze the influence of electronic money on the financial management of Generation Z and to analyze whether the cashless society variable moderates the influence of e-money on the financial management of Generation Z. The population of this study is Generation Z in the city of Pontianak, categorized by age between 20-24 years, amounting to 55,231 people. The research method used is quantitative, by distributing questionnaires to respondents. The analytical method used is simple regression analysis, with the analysis tool being SPSS for Windows version 29. The test results show that the e-money usage variable does not have a significant effect on the financial management of Generation Z. On the other hand, the cashless society variable can moderate and strengthen the effect of e-money on the financial management of Generation Z.